Cochlear Implantation in Single-Sided Deafness and Asymmetric Hearing Loss: 12 Months Follow-up Results of a European Multicenter Evaluation - Thomas Wesarg; Antje Aschendorff; Regina Baumgaertel; Julia Böttcher; Liesbeth De Coninck; Ingeborg Dhooge; Ann Dierckx; Thomas Klenzner; Philipp Schörg; Georg Sprinzl; Freya Swinnen; Nicolas Verhaert; et al. (Journal of International Advanced Otology)
Background: People with single-sided deafness (SSD) or asymmetric hearing loss (AHL) have particular difficulty understanding speech in noisy listening situations and in sound localization. The objective of this multicenter study is to evaluate the effect of a cochlear implant (CI) in adults with single-sided deafness (SSD) or asymmetric hearing loss (AHL), particularly regarding sound localization and speech intelligibility with additional interest in electric-acoustic pitch matching.